The Effect of Corporate Social Responsibility on Financial Performance of Banks in Indonesia: The Role of Intellectual Capital and Bankruption Risk - Marchyta, Nony Kezia; Devie,; Semuel, Hatane (International Journal of Psychosocial Rehabilitation, 2020)
Banking subsector is an institution that relies heavily on public trust, reputation and corporate image, so companies in the banking sub-sector are expected to be more likely to engage in CSR activities to maintain the company's sustainability. There are gaps related to the concept of CSR and it is quite controversial. This research aims to observe the direct impact of CSR towards financial performance, and indirect impact of CSR towards financial performance through intellectual capital and bankruption risk as mediating variables from banking subsector. This study is a quantitative form and the data is obtained from annual report of banking companies listed in IDX from 2011 to 2015. The results show positive impact of CSR towards financial performance and intellectual capital, and intellectual capital towards financial performance. This research also shows negative impact of intellectual capital and CSR towards bankruption risk, and bankruption risk towards financial performance. Finally, banking subsector companies need to increase the intensity of CSR activities and the development of intellectual capital should be a concern as a strategy to achieve competitive advantage in the face of increasingly tight business competition.